The enclosure of ocean resources : - Eckert, Ross D. (Hoover Institute Press, 1979)
This book provides a comprehensive introduction to the economic uses of oceanic resources, the rights to exploit them and the division of the economic rents, or surpluses, between, at one level, sovereign powers, and at another between individual users that use ocean space.Oceanic resources are diverse. Offshore oil deposits are the most valuable oceanic resource measured by the dollar value of annual production but other mineral resources including manganese, shale and sand are also important along with marine mammal resources, fisheries and sea birds.